2018
DOI: 10.1186/s12916-018-1186-4
|View full text |Cite
|
Sign up to set email alerts
|

Baseline exposure, antibody subclass, and hepatitis B response differentially affect malaria protective immunity following RTS,S/AS01E vaccination in African children

Abstract: BackgroundThe RTS,S/AS01E vaccine provides partial protection against malaria in African children, but immune responses have only been partially characterized and do not reliably predict protective efficacy. We aimed to evaluate comprehensively the immunogenicity of the vaccine at peak response, the factors affecting it, and the antibodies associated with protection against clinical malaria in young African children participating in the multicenter phase 3 trial for licensure.MethodsWe measured total IgM, IgG,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
94
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 68 publications
(102 citation statements)
references
References 49 publications
7
94
1
Order By: Relevance
“…Clinical trials on RTS,S showed that the protective response induced by the vaccine fades rapidly; however, whether this is related to specific features of the CSP antigen, or of the HBsAg carrier, or both has not yet been elucidated. Recent analyses of phase III trials suggest that lots of factors are at play in determining the efficacy of RTS,S-induced protection and antibodies levels and decay, such as age, malaria exposure, IgG subclasses, all of which might have different impact on different antigens (50,51). An interesting observation from Ubillos et al (50) was that higher anti-HBsAg antibody levels were associated with less malaria disease risk in RTS,S vaccinees, and further investigation will be needed to explain such a finding.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical trials on RTS,S showed that the protective response induced by the vaccine fades rapidly; however, whether this is related to specific features of the CSP antigen, or of the HBsAg carrier, or both has not yet been elucidated. Recent analyses of phase III trials suggest that lots of factors are at play in determining the efficacy of RTS,S-induced protection and antibodies levels and decay, such as age, malaria exposure, IgG subclasses, all of which might have different impact on different antigens (50,51). An interesting observation from Ubillos et al (50) was that higher anti-HBsAg antibody levels were associated with less malaria disease risk in RTS,S vaccinees, and further investigation will be needed to explain such a finding.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast no relationship was observed between antibody titer and the magnitude of boosting for C-terminal antibodies at any timepoint (Figure 7F). It is notable that C-terminal antibodies have been associated with protection by the RTS, S vaccine 42, 43 . Overall these data strongly support the hypothesis that epitope masking rather than parasite clearance of Fc mediated immune regulator mechanisms account for antibody feedback not only in the mouse model but also in vaccinated individuals.…”
Section: Resultsmentioning
confidence: 99%
“…found that only concentrations of IgG3 specific for blood stage antigens were associated with reduced risk of infection in Senegal 43 . Studies with the RTS,S/AS01E vaccine in Mozambique and Ghana found protection against sporozoite mediated infection positively associated with concentrations of IgG1 and IgG3 antibodies specific for vaccine antigens 44 . These human antibody isotypes are important in mediating antibody-dependent cellular cytotoxicity and complement dependent killing, as are the mouse IgG2b and 2c isotypes elicited by AddaVax, but not alum, in the current study.…”
Section: Discussionmentioning
confidence: 98%